Screening of differentially expressed immune-related genes from spleen of broilers fed with probiotic Bacillus cereus PAS38 based on suppression subtractive hybridization. - Jiajun Li; Wanqiang Li; Jianzhen Li; Zhenhua Wang; Dan Xiao; Yufei Wang; Xueqin Ni; Dong Zeng; Dongmei Zhang; Bo Jing; Lei Liu; Qihui Luo; et al. (PLoS ONE)
The aim of this study was to construct the spleen differential genes library of broilers fed with probiotic Bacillus cereus PAS38 by suppression subtractive hybridization (SSH) and screen the immune-related genes. Sixty seven-day-old broilers were randomly divided into two groups. The control group was fed with basal diet, and the treated group was fed with basal diet containing Bacillus cereus PAS38 1×106 CFU/g. Spleen tissues were taken and extracted its total RNA at 42 days old, then SSH was used to construct differential gene library and screen immune-related genes. A total of 119 differentially expressed sequence tags (ESTs) were isolated by SSH and 9 immune-related genes were screened out by Gene ontology analysis. Nine differentially expressed genes were identified by qRT-PCR. JCHAIN, FTH1, P2RX7, TLR7, IGF1R, SMAD7, and SLC7A6 were found to be significantly up-regulated in the treated group. Which was consistent with the results of SSH. These findings imply that probiotic Bacillus cereus PAS38-induced differentially expressed genes in spleen might play an important role in the improvement of immunity for broilers, which provided useful information for further understanding of the molecular mechanism of probiotics responsible to affect the poultry immunity.